IMPLEMENTASI PENDIDIKAN KARAKTER SEMANGAT KEBANGSAAN DALAM PEMBELAJARAN TEMATIK TERPADU DI SDN 46 KOTA SINGKAWANG - Widi Astuti; Aunurrahman Aunurrahman; Sulistyarini Sulistyarini (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
ABSTRACTThis study aims to describe the implementation of the character education of thenational spirit in integrated thematic learning at 46 Public Schools in SingkawangCity. This research is a descriptive study with a qualitative approach. The subjectsof this study were principals, teachers and participants in SD Negeri 46 KotaSingkawang. The data was collected by observing, interviewing and documenting.Data analysis was carried out in stages: data reduction, data display, and drawingconclusions. Data validity checking techniques using technical triangulation anddata source triangulation. The results show that the analysis of national spiritcharacter education in thematic learning at 46 Elementary Schools in Singkawangis as follows: (1) the planning is that the teacher has included the character of thenational spirit in the lesson plan, the components in the lesson plan are inaccordance with existing guidelines, (2) In its implementation, students havecarried out activities related to the character of the national spirit, so that anattitude of tolerance and mutual respect is achieved (3) in assessment activities,the teacher carries out authentic assessments and attitude assessments. Assessmentof students' attitudes, namely honesty, discipline, responsibility, courtesy and thecharacter of the national spirit.Keywords: Character of the Spirit of Nationality, Integrated Thematic Learning.